Study on the formation process of low‐temperature ash deposition induced by ammonium bisulfate in pulverized coal‐fired boiler. Issue 1 (19th November 2019) - Wang, Limin; Bu, Yufan; Tang, Chunli; Lv, Cheng; Chen, Xun; Che, Defu
Abstract: In order to explore the mechanism of low‐temperature ash deposition induced by ammonium bisulfate (ABS), ash deposits, and a corroded heat transfer plate in the rotary air preheater (RAPH) of a 1, 000‐MW pulverized coal‐fired power plant in China were analyzed by X‐ray fluorescence, ion chromatography, X‐ray diffraction, and scanning electron microscope equipped with energy dispersive X‐ray spectroscopy. The element composition, main compounds, and ammonium ion in the samples were analyzed. The thermal gravimetric analysis of ash samples was conducted to infer the type of ammonium salt ultimately existing in the ash. The prediction of the ABS deposition range coincides well with both the area of serious ash deposition and the area of NH4 + distribution obtained by ion chromatography. The cause for corrosion and plugging in the RAPH was proposed by analyzing the reactions or mineral transformations involved in the ash deposits. The results indicate that ABS can form in a large height range in the RAPH. The ammonium induces the sulfur trioxide to deposit on and react with the metal plate or the ash particles to form sulfates, which act as the bridging agent, finally leading to serious plugging problems in the RAPH.